Holographic Microwave Imaging for Lesion Detection - Wang, Lulu (Auckland University of Technology, 2013)
This thesis presents the preliminary analysis and development of a novel technique to detect inclusion in a dielectric object that is based on holographic microwave imaging array (HMIA) and aperture synthesis far-field imaging techniques. This new microwave based approach may have a potential to become an imaging tool for breast lesion detection in the future. The two dimensional (2D) and three dimensional (3D) computer simulation models have been developed using MATLAB to demonstrate the 2D and 3D HMIA image reconstruction algorithms. A suitable antenna for experimental implementation using HMIA techniques is designed, and the spiral and random antenna array configurations are developed to significantly improve the quality of the images. The proposed technique has been validated through simulation and measurements on multiple dielectric objects (breast phantoms). Results have demonstrated the feasibility and superiority of detecting small inclusions (lesions) in the breast model using the HMIA imaging algorithms. The achieved simulation and experimental images using different antenna array configurations have been evaluated using visual inspection and quantitative analysis methods. Results show that the spiral and random antenna array configurations have the ability to produce better quality images compare to the most widely used regularly spaced array. Finally, the 2D HMIA technique has been applied on 2D and 3D head models for brain stroke detection. The Method of Moments (MoM) and Born approximation approaches are employed to solve the scattering electric field of 2D and 3D head models respectively. The simulation results indicate that the HMIA technique has a potential for other medical imaging applications, such as brain stroke detection.
Keywords: Holographic Microwave Imaging; Lesion Detection; Aperture Synthesis; Far Field; Antenna Array